Factors associated with gym-based fitness injuries: A case-control studyPractical implications: - L. Noteboom; E. Kemler; A.M.C. van Beijsterveldt; M.J.M. Hoozemans; F.C.T. van der Helm; E.A.L.M. Verhagen (Elsevier, 2023)
Objectives: A large number of sports injuries are sustained during gym-based fitness activities. As a first step towards prevention, the objective of the present study was to identify factors associated with fitness injuries. Design: Retrospective case-control study. Methods: 493 fitness participants that sustained a fitness injury in the past year (cases) were compared to 971 fitness participants that did not sustain a fitness injury (controls), regarding their characteristics and their exposure to gym-based fitness activities, other sports, and work. Multiple logistic regression was performed to identify factors associated with fitness injuries. Results: Males were 1.7 times (95% CI [1.4, 2.1]) more likely than females to have sustained an injury (univariate Odds Ratio). Identified injury associated factors from the final prediction model for males included: age below 41, 7+ months fitness experience, performing fitness mainly outdoors or indoors (vs. at-home), and combining 5+ times fitness per month with full-time work. The goodness of fit of the final model for males was sufficient (Area Under the Curve (AUC) ​= ​0.73), while the final model for females had a poor fit (AUC ​= ​0.6). Conclusions: Young males were more associated with fitness injuries, potentially due to different 'risk-taking' behavior or training intensity compared to elder people and females. Results suggest that factors outside of fitness, like work, may contribute to injury occurrence and should be considered when designing a training schedule to prevent overall (physical and mental) overload. Furthermore, at-home fitness was associated with fewer injuries compared to indoor or outdoor fitness. Future longitudinal research is needed to identify cause-effect relationships.